Acanthosis nigricans-like diaper dermatitis. - Gelmetti, C.; Ranzi, M.L.; Caputo, R. (European Journal of Pediatric Dermatology, 2018)
Diaper dermatitis is a common designation for a variety of inflammatory disorders that occur in infants in the area covered by a diaper. Most commonly this disorder results from the effects of occlusion and chafing; microorganisms, especially Candida albicans, but also bacteria can play a role. The disease is represented by inflamed lesions circumscribed to convex surfaces of the pubic region, genitalia, buttocks, and upper part of the thighs or by erythema of the intertriginous areas. Tiny pustules at the periphery of the lesions are also a common sign; fully evolved or ulcerated papules or nodules or red-brown dark tumoral lesions are more rarely seen. We report three infants affected by a curious form of diaper dermatitis characterized by an acanthosis nigricans-like appearance involving the inguinal and sovrapubic folds. Histology performed in one case revealed hyperkeratosis with parakeratosis and bacteria (Enterococcus faecalis) invading the outer part of the epidermis. Lesions disappeared in all cases in a time variable from a few days to a few months with a mild topical treatment. This variety of diaper dermatitis, to our knowledge, has never been described so far.